In Silico Screening of Syzygium myrtifolium Flavonoid Compoinds as Anti-bacterial Activity: In Silico Screening of Syzygium myrtifolium Flavonoid Compounds - Jatmiko Eko Witoyo; Masruri; Sudarminto Setyo Yuwono; Simon Bambang Widjanarko; Nelsy Dian Permatasari (Journal of Tropical Life Science, 2022)
Bacterial infection and antibiotic resistance are popular issues nowadays. Several pre[1]vious reports performed antibacterial screening activities involving natural herbs and synthetic drugs. Alanine racemase and transglycosylase are essential proteins for peptidoglycan membrane synthesis in bacteria and an alternative target for antibacterial performance. This study identified six flavonoid compounds in Syzygium myrtifolium to perform the antibacterial activity. In silico study was conducted for modelling flavonoids – protein complexes. Five flavonoids from S. myrtifolium were taken out of he canonical smiles from the PubChem database and modelled three-dimensional structure using ChemDraw and molView. Targeted protein, alanine racemase and transglycosylase were downloaded from Protein Data Bank with ID 4WR3 and 1SLY. Ligands and proteins were interacted by Molegro virtual Docker 5.0 and visualized by Discovery studio version 21.1.1. Five flavonoids showed inhibition with alanine racemase and transglycosylase in the same active sites of control and sodium benzo[1]ate. According to the binding energy, calopiptin performed the lowest binding energy value in alanine racemase complexes, while 2-Propanone, 1,3-bis(5-nitro-2-furanyl) showed the lowest value of four other flavonoids at transglycosylase complexes. The type of interactions were electrostatic, hydrogen bonds, hydrophobic interactions and unfavorable ones. Low binding energy and varied interaction types indicated tight of ligand-protein interaction. In summary, five flavonoids inhibited alanine racemase and transglycosylase, and the peptidoglycane membrane synthesis in bacteria might be inferred.